2016
DOI: 10.2217/nnm-2016-0207
|View full text |Cite
|
Sign up to set email alerts
|

Active Diffusion of Nanoparticles of Maternal Origin Within the Embryonic Brain

Abstract: PSi NPs penetrate deep in the brain tissues of embryos after intraventricular injection and after iv. injection to the mother.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…We recently developed an in vivo two-photon method to image calcium activity in the mouse embryonic cortex 24 , 25 . We previously showed that there is a remarkable selectivity of the loading of the Fluo-4AM dye for cell populations closer to the cortical plate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We recently developed an in vivo two-photon method to image calcium activity in the mouse embryonic cortex 24 , 25 . We previously showed that there is a remarkable selectivity of the loading of the Fluo-4AM dye for cell populations closer to the cortical plate.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, only the native in vivo environment can reflect the full complexity of interactions between blood flow and the active cells. Recent significant advances in the field of two-photon imaging 16 , 17 , 24 , 25 , 32 , 33 , allow the imaging of developmental processes while maintaining physiological conditions of live embryos. In the present work, we implement this method for calcium imaging of the cortex in embryos connected to the mother through the umbilical cord.…”
Section: Discussionmentioning
confidence: 99%